O modelo cooperativo de processo na perspectiva do pragmatismo de Peirce - Fortuna, Marcelo Forli (2018)
The present work aims to analyze the dynamics of the Law and its moment of realization from the Peircian pragmatism, in a Democratic Constitutional model of process. The science of law, seen as a living science, when carried out in a concrete case, goes, necessarily when there is litigation, through a judicial process. It is in the daily routine of our courts that rights are effective and that conflicts are pacified. The construction of the norm is made necessarily from the factual narratives strategically elaborated by the lawyers who try, over the course of the deed, to convince the judge about its assertions. Peirce's philosophy assists us in understanding that, even though the sentence concretizes the decision, this one is formed along the procedural course, from the creative reason, which combines practical and theoretical reason in a coherent way with the abductive, inductive and deductive models of inference, without leaving aside ethics and aesthetics. During the process, the judge generates and selects hypotheses, conjectures consequences, and develops the inductive test at the time of probationary instruction, all in conjunction with the parties. The cooperative process model, viewed from the perspective of Peirce's pragmatism, develops in a democratic way, in a real working community, aiming at a rational decision. The emphasis on fallibilism and its relevance in the perceptions judgment reinforces the need to favor sanitation in cooperation and reinforcement of the contradictory. The sentence, with its logical, ethical and aesthetic dimensions, concretizes not only the context of justification, but also the whole decision context that was constructed from the real contribution of the parties, reducing the degree of fallibilism. The precedents and jurisprudence, therefore, assume relevance in the construction of the habits that will delimit the new judgments of perception, allowing greater stability, coherence and integrity of the system